Design of compact planar crossover using Sierpinski carpet microstrip patch. Issue 1 (1st January 2013) - Henin, Bassem; Abbosh, Amin
Abstract : The design of a planar four‐port microstrip crossover is presented. The design starts by using a half‐wavelength square patch and two sets of orthogonal feeding lines. Based on the cavity theory, operation of the patch crossover is analysed. Full‐wave simulations and measurements are used to support the analysis. By etching the patch as a Sierpinski carpet, resonant frequency can be lowered significantly, and this property can be employed to reduce the size of the conventional patch crossover. It is shown that the size of the crossover can be reduced by 23% with even a better performance when a second‐order Sierpinski carpet microstrip patch is used. Full‐wave simulations and measurements are used to validate the proposed design method. The measured data show less than 1 dB insertion loss, more than 10 dB return loss, more than 17 dB isolation and about 0.1 ns group delay deviation across 10% fractional bandwidth centred at 2.4 GHz.